2023
DOI: 10.1029/2022ja031115
|View full text |Cite
|
Sign up to set email alerts
|

Storm Time Electrified MSTIDs Observed Over Mid‐Latitude North America

Abstract: Traveling Ionospheric Disturbances (TIDs; Munro, 1948) are wave-like structures which propagate through the ionosphere. TIDs are most commonly expected to be driven by Atmospheric Gravity Waves (AGWs) originating in the neutral atmosphere (Hines, 1960) and can be sensed with instruments used for monitoring ionospheric dynamics such as Global Navigational Satellite Service (GNSS) Total Electron Content (TEC;Saito et al., 1998) and coherent scatter radars (Fukao et al., 1991;Samson et al., 1990). TIDs are furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 84 publications
(174 reference statements)
1
8
0
Order By: Relevance
“…At high latitudes, electric fields may play an active role in the triggering as well as horizontal propagation of TIDs. Such electric field oscillations were previously indicated during MSTID occurrence (Kelley et al, 2023). Therefore, we examined the presence of significant ion velocity oscillation in the EISCAT measurements.…”
Section: Energy Inputs From Joule Heating and Particle Precipitations...mentioning
confidence: 71%
See 1 more Smart Citation
“…At high latitudes, electric fields may play an active role in the triggering as well as horizontal propagation of TIDs. Such electric field oscillations were previously indicated during MSTID occurrence (Kelley et al, 2023). Therefore, we examined the presence of significant ion velocity oscillation in the EISCAT measurements.…”
Section: Energy Inputs From Joule Heating and Particle Precipitations...mentioning
confidence: 71%
“…EISCAT IS radar measurements of electron density have been used to study the propagation characteristics of LSTIDs (Cai et al., 2011; Ma et al., 1998) as well as Medium‐Scale TIDs (MSTIDs), which are often forced by upward‐propagating gravity waves (Günzkofer et al., 2023; Hocke & Schlegel, 1996; Kirchengast et al., 1996; Vlasov et al., 2011). Other forcing mechanisms include interhemispheric electrodynamic coupling along magnetic field lines (Otsuka et al., 2004; Shiokawa et al., 2005; Tsunoda & Cosgrove, 2001) and storm time electric fields which can force TIDs electrodynamically, for example, via the Perkins instability (Kelley et al., 2023; Tsugawa et al., 2007; Zhang et al., 2019, 2022). IS radar can also measure the oscillation period and the vertical wavelength associated with generated gravity waves with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Those values could be caused by the relative velocity between the E ‐region NREs and the F ‐region MSTIDs switching the electric field polarities between the crests and the troughs (Kelley et al., 2023). Either positive or negative polarization electric field is mapped down to the E ‐region to affect the NREs (Hiyadutuje et al., 2022).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Examples of BLISS in GNSS TEC (Figure 8) also reveal similar structures, where the depletion channel is sandwiched between high‐density regions. Some studies have indicated that the presence of such sandwiched density gradient structures at midlatitude ionosphere is likely associated with SAPS and polarization electric fields (I. J. Kelley et al., 2023; S.‐R. Zhang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with our first explanation that high‐altitude/latitude EPB/ESF structures can indeed intrude into the midlatitude region under strong PPEF condition. On the other hand, some studies using Super Dual Auroral Radar Network (SuperDARN) and GNSS TEC measurements have observed polarities switching of plasma velocities between midlatitude MSTID‐like electron density crests and troughs under background SAPS electric fields, indicating the presence of polarization electric fields and associated electrodynamic/Perkins instability processes (I. J. Kelley et al., 2023; S.‐R. Zhang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%